Criminal Offense of Fraud Against Misuse of Funds Donations on Behalf of Al Kahfi Islamic Boarding School in Kebumen District - Sahrul Rizqi Ramadhani (Proceedings Series on Social Sciences & Humanities, 2023)
This research aims to analyse the crime of fictitious donation and its implications in the context of financial crime. Fictitious donation is an act that involves manipulating or falsifying information to obtain donations that do not actually exist. This article explains how fictitious donation crimes occur in practice and their impact on victims, society, and the financial system. The research method used in this study is a normative analysis based on secondary data, including investigation reports, court judgements, and related literature. To gain a deeper understanding of the issue. The results show that fictitious donation crimes have various forms of execution, including the creation of fake entities, and document forgery. The motives behind these crimes are often related to financial gain. The impact of fictitious donation crimes can be devastating. The main victims are the donation recipients who should have received the funds, but did not because the resources were diverted to the fake entity. In addition, society as a whole can also be affected due to the loss of trust in organisations or institutions that practice fictitious donations. The financial system is also threatened by this crime, as it can undermine the integrity and transparency of financial reporting. To address the crime of fictitious donations, this research recommends strengthening cooperation between law enforcement agencies and the government. There is a need to raise awareness of the risks associated with fictitious donations, and improve regulation and supervision to prevent and detect such acts.